Ion-Energy Dependence of Asymmetric Dissociation of D2 by a Two-Color Laser Field - Ray, D.; He, F.; De, S.; Cao, W.; Mashiko, H.; Ranitovic, P.; Singh, K. P.; Znakovskaya, I.; Thumm, U.; Paulus, G. G.; Kling, M. F.; Litvinyuk, I. V.; et al. (My University, 2009)
Two-color (800 and 400 nm) short (45 fs) linearly polarized pulses are used to ionize and dissociate D2 into a neutral deuterium atom and a deuteron. The yields and energies of the ions are measured left and right along the polarization vector. As the relative phase of the two colors is varied, strong yield asymmetries are found in the ion-energy regions traditionally identified as bond softening, above-threshold dissociation and rescattering. The asymmetries in these regions are quite different. A model based on the dynamic coupling by the laser field of the gerade and ungerade states in the molecular ion accounts for many of the observed features.